Problems of safety of food products - Grigorenko, Inna; Chorna, Anastasia (My University, 2013)
Вибір стандартів імпортної та національної продукції повинен виконуватися відповідно до правила і має певні особливості. До таких особливостей, наприклад, очевидні суперечності в документації.The selection of standards of the imported and national products must be executed in accordance with the rules and has certain features. To such features, for example, obvious inconsistencies in documentation.
Keywords: safety; food products; безпечність; харчові продукти; кафедра експертизи харчових продуктів